Innovations as Key to the Green Revolution in Africa 2011
DOI: 10.1007/978-90-481-2543-2_10
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer Microdosing and “Warrantage” or Inventory Credit System to Improve Food Security and Farmers’ Income in West Africa

Abstract: The fertilizer microdosing technology deals with the application of small quantities of fertilizers in the planting hole, thereby increasing fertilizer use efficiency and yields while minimizing input costs. In drought years, microdosing also performs well, because larger root systems are more efficient at finding water, and it hastens crop maturity, avoiding lateseason drought. Recent research found that solving the soil fertility problem unleashes the yield potential of improved millet varieties, generating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 5 publications
1
23
1
Order By: Relevance
“…The warrantage system appears therefore as a community-based micro credit scheme which is affordable to poor small scale households (Adamu and Chianu, 2011;Tabo et al, 2011, Sogodogo et al, 2014. Among other sources of funds, it is the most considered by famers (Poulton et al, 2006;Adesina, 2009;Zoundi and Hitimana, 2011), and more suited to the socio-economic conditions of poor farmers.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The warrantage system appears therefore as a community-based micro credit scheme which is affordable to poor small scale households (Adamu and Chianu, 2011;Tabo et al, 2011, Sogodogo et al, 2014. Among other sources of funds, it is the most considered by famers (Poulton et al, 2006;Adesina, 2009;Zoundi and Hitimana, 2011), and more suited to the socio-economic conditions of poor farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Daoudi and Wampfler (2010), Beaman et al (2014), Banerjee et al (2015) and Crépon et al (2015) showed that the agricultural credit promoted the adoption of innovations. This micro-credit strongly influences the attendance to inputs shops and therefore enables farmers to acquire fertilizer and other agricultural inputs (Buerkert et al, 2001;Tabo et al, 2011, Sogodogo et al, 2014.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations